Perancangan Enterprise Architecture Pada Perusahaan Operator Kereta Api Menggunakan Metode Togaf ADM - Dodi Permadi (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2021)
The Railway network has been the backbone of many cities around the world. Solving traffic congestion problems from excessive use of private vehicles. High mobility is one of the traits in modern society and most governments are obligated to provide high standard public services. But having a railway operator does not come at a cheap price, yet it becomes a burden when it wrongly manages. Railway operators as public transportation companies should have strategic planning on how to be independent financially and profitable. The company should adopt technology to create operational efficiency, lean organization structure and unfolded possibilities of getting multiple revenue streams. Thereby Enterprise Architecture (EA) is the remedy, a foremost framework which connects business processes, information systems, and information technology in the easiest way to digest. The author would like to propose an EA concept using TOGAF ADM phases for railway operators based on literature study. The purpose of this paper is to give insight and supposedly help any railway operators company get a better perspective on the use of EA.